Case Report: Profound newborn leukopenia related to a novel RAC2 variant - Hall, Geoffrey; Donkó, Ágnes; Pratt, Cristina; Kim-Chang, Julie J.; Martin, Paul L.; Stallings, Amy P.; Sleasman, John W.; Holland, Steven M.; Hsu, Amy P.; Leto, Thomas L.; Mousallem, Talal (Frontiers in Pediatrics, 2024)
We report a 1-week-old male born full-term with two inconclusive severe combined immunodeficiency (SCID) newborn screens who developed scalp cellulitis and E. coli bacteremia. He did not pass early confirmatory hearing screens. Initial blood counts and lymphocyte flow cytometry revealed profound neutropenia and lymphopenia with a T-/B-/NK-phenotype. Red blood cell adenosine deaminase 1 activity was normal. A presumptive diagnosis of reticular dysgenesis was considered. Granulocyte-colony stimulating factor was started without improvement in neutrophil counts. Subsequent lymphocyte flow cytometry at around 4 weeks of age demonstrated an increase in T-, B-and NK-cell numbers, eliminating suspicion for SCID and raising concern for congenital neutropenia and bone marrow failure syndromes. Genetic testing revealed a novel variant in RAC2 [c.181C>A (p.Gln61Lys)] (Q61K). RAC2, a RAS-related GTPase, is the dominant RAC protein expressed in hematopoietic cells and is involved with various downstream immune-mediated responses. Pathogenic RAC2 variants have significant phenotypic heterogeneity (spanning neutrophil defects to combined immunodeficiency) across dominant, constitutively activating, dominant activating, dominant negative, and autosomal recessive subtypes. Given the novel variant identified, functional testing to evaluate aberrant pathways described in other RAC2 pathogenic variants was pursued. In comparison to wild-type RAC2, the Q61K variant supported elevated superoxide production under both basal and PMA-stimulated conditions, increased PAK1 binding, and increased plasma membrane ruffling consistent with other dominant, constitutively-active mutations. This case highlights the diagnostic challenge associated with genetic variants identified via next generation sequencing panels and the value of functional assays to confirm variant pathogenicity.